Artificial Intelligence In The Realm Of Fatwa: An Analytical Study On Its Use As A Reference Tool In Malaysia - Khairul Azhar Meerangani; Muhammad Ikhlas Rosele; Mohammad Fahmi Abdul Hamid; Ibrahim Adham Mohd Rokhibi (Universiti Sains Islam Malaysia, 2026)
The rapid advancement of Artificial Intelligence (AI) technologies has significantly transformed various sectors, including Islamic legal research and fatwa issuance. This study examines the feasibility of using AI as a reference tool in the domain of fatwa, focusing specifically on its application within the Malaysian context. By analysing relevant fatwa frameworks, institutional practices, and the epistemological foundations of Islamic legal decision-making, this research explores the potential benefits, limitations, and ethical concerns associated with integrating AI technologies into fatwa processes. The study employs a qualitative analytical approach, including document analysis and expert interviews, to evaluate the extent to which AI can support, but not replace, the role of human muftis and fatwa committees. Findings suggest that while AI offers significant utility in data retrieval, pattern recognition, and preliminary legal referencing, its limitations in contextual reasoning (waqi‘), moral judgement, and ijtihad highlight the need for strict epistemic boundaries. The integration of AI must also be guided by the Islamic principle of tabayyun (critical verification), ensuring that digital information used in fatwa development is rigorously evaluated in both form and substance. The paper concludes with proposed ethical and operational guidelines for incorporating AI into fatwa management, advocating a complementary model that upholds the sanctity and authority of traditional Islamic jurisprudence.